2010
DOI: 10.3347/kjp.2010.48.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Delayed Human Neutrophil Apoptosis by Trichomonas vaginalis Lysate

Abstract: Neutrophils play an important role in the human immune system for protection against such microorganisms as a protozoan parasite, Trichomonas vaginalis; however, the precise role of neutrophils in the pathogenesis of trichomoniasis is still unknown. Moreover, it is thought that trichomonal lysates and excretory-secretory products (ESP), as well as live T. vaginalis, could possibly interact with neutrophils in local tissues, including areas of inflammation induced by T. vaginalis in humans. The aim of this stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 28 publications
0
15
0
Order By: Relevance
“…Controversial studies have been published concerning cytokines profile that may be induced in response to T. vaginalis infection. Some previous studies in vitro revealed that exposure to T. vaginalis stimulated IL-8 secretion in human monocytes, [21] neutrophils, [22] and vaginal epithelial cells. [23] It was further demonstrated that the cytokines IL-2 and IFN-γ were secreted by murine lymphocytes infected with T. vaginalis.…”
Section: Discussionmentioning
confidence: 99%
“…Controversial studies have been published concerning cytokines profile that may be induced in response to T. vaginalis infection. Some previous studies in vitro revealed that exposure to T. vaginalis stimulated IL-8 secretion in human monocytes, [21] neutrophils, [22] and vaginal epithelial cells. [23] It was further demonstrated that the cytokines IL-2 and IFN-γ were secreted by murine lymphocytes infected with T. vaginalis.…”
Section: Discussionmentioning
confidence: 99%
“…T. vaginalis lysate and ESP were prepared as described previously [17] . To prepare the lysate, T. vaginalis trophozoites were harvested in logarithmic growth phase and washed three times in PBS (pH 6.2).…”
Section: Methodsmentioning
confidence: 99%
“…Stimulation with TvSP for IL-8 production in neutrophils Neutrophils (1 9 10 5 ) were seeded in 96-well tissue culture plates and then directly incubated for the times indicated with or without TvSP [6], pretreated TvSP or modified TvSP at 37°C in a 5% CO 2 incubator. No cytotoxicity of lipase or proteinase K alone was observed.…”
Section: Isolation Of Human Neutrophilsmentioning
confidence: 99%
“…In addition, in-vitro experiments indicate that actively rotating T. vaginalis harbors and secretes various immunological stimuli, which might lead to vaginal mucosal inflammation. One study showed that the longevity of human neutrophils is prolonged in response to T. vaginalis lysate [6]. Another study showed that human neutrophils or macrophages stimulated with live T. vaginalis produce the chemokine interleukin (IL)-8 and the proinflammatory cytokines tumor necrosis factor-a, IL-6, and IL-1b [7,8].…”
Section: Introductionmentioning
confidence: 99%